FORMULATION AND DEVELOPMENT OF CURCUMIN BASED EMULGEL IN TREATMENT AND RECURRENCE OF VAGINAL CANDIDIASIS - BAIRAGI, GHANSHAMDAS R.; PATEL, VIPUL P. (International Journal of Current Pharmaceutical Research, 2021)
Objective: The main causative agent of vaginal candidiasis is Candida albicans and it develops resistance against several synthetic antifungal drugs and it has a high rate of infection in women. According to WHO report, around 75% of women are infected by Candida albicans and 50 % are infected a second time by Candida albicans. Therefore, we choose Curcumin an antifungal agent that had reported antifungal properties against the various fungal species. The Curcumin-containing emulgel based microemulsion system was prepared for greater retention time and penetration across the vaginal mucosa. Methods: The screening of oil phase, surfactant, and cosurfactant for microemulsion formulation was selected based on the solubility study and followed by the construction of the pseudoternary phase diagram. The oil phase, surfactant and co-surfactant are selected from the pseudoternary phase diagram for the formulation of a stable microemulsion. The prepared Curcumin-loaded microemulsion was characterized by globule size, polydispersity index, Zeta potential, accelerated stability study, drug content, percent transmittance and antifungal assay by broth microdilution technique. The formulated microemulsion was converted into a vaginal emulgel by using Pluronic@F127. The formulated curcumin-loaded emulgel was characterized by different evaluation parameters and antifungal study by agar well diffusion method. Results: The result showed that the average globule size of emulgel was 286.3 nm, polydispersity index was 0.241, Zeta potential was+19.20 mv, conductivity was 0.0390 mS/cm, and drug content was found to be 95.58%. The texture of formulated emulgel was found to be soft and smooth, with shear-thinning, pseudoplastic behavior, and easily spreadable. The in vitro permeability study of emulgel shows slow and complete release of curcumin in 10 h. The microemulsion and developed emulgel showed promising antifungal activity against Candida albicans. Conclusion: The developed curcumin-loaded emulgel showed promising antifungal activity against Candida albicans as compared to the Fluconazole as an standard antifungal antibiotic. Our formulated Curcumin-containing emulgel can be a potential alternative as compared to the conventional dosage form for the treatment of vaginal candidiasis.